Prognostic significance of deregulated dicer expression in breast cancer. - Emer Caffrey; Helen Ingoldsby; Deirdre Wall; Mark Webber; Kate Dinneen; Laura S Murillo; Celine Inderhaug; John Newell; Sanjeev Gupta; Grace Callagy (PLoS ONE, 2013)
BACKGROUND: Dicer, an RNase III-type endonuclease, is the key enzyme involved in RNA interference and microRNA pathways. Aberrant expression of Dicer is reported in several human cancers. Our aim was to assess the prognostic role of Dicer in breast cancer. METHODS: The entire series comprised 666 invasive breast cancers (IBCs), 480 DCIS cases (397 associated with IBC and 83 pure DCIS) and 305 lymph node metastases. Cytoplasmic Dicer expression by immunohistochemistry was scored as negative (no staining) and positive (weak, moderate or strong staining). RESULTS: Dicer staining was assessable in 446 IBC, 128 DCIS and 101 lymph node metastases. Expression of Dicer was observed in 33% (145/446) of IBCs, 34% (44/128) of DCIS and 57% (58/101) of lymph node metastases. Dicer expression was increased in nodal metastases compared to primary tumours (p<0.001); and was associated with ER negativity (p<0.001), HER2 positivity (p<0.001), high Ki67 labeling index (p<0.001) and expression of basal-like biomarkers (p = 0.002). Dicer positivity was more frequent in the HER2 overexpressing (p<0.001) and basal-like (p = 0.002) subtypes compared to luminal A subtype. Dicer expression was associated with reduced overall survival (OS) on univariate analysis (p = 0.058) and remained an independent predictor of OS on multivariate analysis (HR 2.84, 95% CI 1.43-5.62, p = 0.003), with nodal status (HR 2.61, 95% CI 1.18-5.80, p = 0.018) and PR (HR 0.28, 95% CI 0.13-0.59, p = 0.001). Further, moderate or strong expression of Dicer was associated with improved disease-free survival in the HER2-overexpressing subtype compared to negative or weak expression (p = 0.038). CONCLUSION: Deregulated Dicer expression is associated with aggressive tumour characteristics and is an independent prognostic factor for OS. Our findings suggest that Dicer is an important prognostic marker in breast cancer and that its prognostic role may be subtype specific.